Instrumentation considerations of a clinical and a computerized technique for the measurement of foot angles. - Stacpoole-Shea S; Shea G; Otago L; Payne W (Journal of Foot & Ankle Surgery)
Measurement of the foot angles either directly from the patient, from video images, or from radiographs is integral to podiatric clinical practice to confirm diagnoses and to plan, prescribe, and monitor treatment protocols. The reliability, precision, and accuracy involved in any measured value limits the validity and usefulness of the measurement to optimal patient management. Studies are described that ensured the accuracy and validity of the standard clinical tool, the universal goniometer (UG), by applying a calibration protocol. These same calibration angles were then measured by a computer-assisted human movement analysis system, the Ariel Performance Analysis System (APAS). The APAS was found to overestimate consistently the UG angular measures by less than 1 degree and this amount of error was considered clinically irrelevant. The angular results obtained by a clinician and a technician using the APAS on two separate days were tested and were found to be comparable and reliable to within 1 degree, and thus the analysis was deemed to be of excellent reliability and precision. The study found that clinicians could establish the accuracy and validity of their instruments by means of simple calibration, and that computer measures could be repeated on patients by a clinical or a technician. The simple calibration procedure described will assist the clinician to ensure that the measures obtained in the clinical setting have minimal measurement error and that the values can be confidently used to make decisions and draw clinical inferences.